Inflation Risk in the Euro Area — How to Achieve a Soft Landing - Gerhard Illing (Wirtschaftsdienst)
Abstract Whereas strong demand is a key factor driving high inflation in the US, inflation in the Euro Area is mainly due to adverse external supply shocks (in Europe, energy prices are much higher due to the war in Ukraine). Standard monetary policy response to such shocks is to accommodate first-round effects, to fight spiralling inflationary expectations in order to prevent second-round effects. Long run inflation expectations — as measured by the survey of professional forecasters — still seem to be well anchored. The ECB’s announced tightening intends to dampen rising household’s inflation expectations. Given the current high uncertainty about the economic outlook, a soft landing calls for modest, data-dependent steps, allowing for a reversal in case the outlook worsens.